2003
DOI: 10.1002/dc.10247
|View full text |Cite
|
Sign up to set email alerts
|

Telecytology of fine‐needle aspiration biopsies of the pancreas: A study of well‐differentiated adenocarcinoma and chronic pancreatitis with atypical epithelial repair changes

Abstract: Four experienced cytopathologists provided consultations using telecytology and routine microscopy. Twenty-seven fine-needle aspiration biopsies (FNABs) from patients with chronic pancreatitis with atypical epithelial repair changes (n = 9) and pancreatic low-grade adenocarcinomas (LG-AC) (n = 18) were studied. False-positive and false-negative diagnostic rates were 19.4% and 12.5% by microscopy and 11.1% and 2.8% by telecytology. Comparisons of agreements between the correct diagnoses and consultations render… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 21 publications
2
28
0
2
Order By: Relevance
“…However, they were captured by an experienced cytopathologist from optimally prepared specimens and consciously selected fields on the slides. Thus, major limitations, such as unsatisfactory fixation and deficient photographic technique [11,14,28], which frequently hamper the diagnosis on digital images sent via iPath by colleagues from countries with limited resources, were excluded. Importantly, the wet-fixed and mostly Papanicolaou-stained cells remained transparent and allowed the evaluation of the nuclear chromatin pattern as the most important cytological criterion of malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they were captured by an experienced cytopathologist from optimally prepared specimens and consciously selected fields on the slides. Thus, major limitations, such as unsatisfactory fixation and deficient photographic technique [11,14,28], which frequently hamper the diagnosis on digital images sent via iPath by colleagues from countries with limited resources, were excluded. Importantly, the wet-fixed and mostly Papanicolaou-stained cells remained transparent and allowed the evaluation of the nuclear chromatin pattern as the most important cytological criterion of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The latter studies have focused on cervical smears [7,8,9,10,11] or on both gynecological and nongynecological [2] as well as mixed nongynecological cytology [12,13], whereas few have focused on fine-needle aspirations (FNAs) from a single organ like the pancreas [14], thyroid gland [15,16], liver [17] or urinary tract [18]. Most of these studies on telehistology as well as on telecytology report a concordance rate of 80-90% between the diagnoses made on digital images and the reference diagnoses made on the regular glass slides.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers on telecytological evaluation of fine needle aspirations (FNAs) from various body sites have been published [1,2,3,4], but only few papers are available on specimens from one topographic region like the breast [5,6,7], thyroid gland [8,9] or pancreas [10]. The results of these studies indicate that the accuracy of the telecytological diagnoses may considerably depend on the topographic origin of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…The phenotype of HCC is also extremely variable depending on the grade of malignancy - even an adenoid pattern may occur [15]. Moreover, analogous to urothelial lesions, the morphological differentiation between ‘dysplastic' cells and HCC cells may be difficult [10] due to a sliding transition from reactive nuclear changes of cells in a cirrhotic liver to true cancerous atypia [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Ayatollahi et al [30] reported between 83 and 87% accuracy for the interpretation of static images from pleural effusion specimens compared to the final diagnosis versus 89% accuracy for interpretation of the glass slides. In studies of pancreatic fine-needle aspiration biopsies by static images, Marchevsky et al [31] reported improved performance over light-microscopic examination in the discrimination of chronic pancreatitis from low-grade adenocarcinoma. They did report considerable inter- and intraobserver variability in diagnosis, which might be expected for this often difficult discrimination, but less was reported using the static-image approach.…”
Section: Telediagnosis/teleconsultationmentioning
confidence: 99%